Design and development of a prototype charge controller for a PV-battery-generator hybrid power system / Sulaiman Shaari, Anuar Ahmad and Shahril Irwan Sulaiman - Shaari, Sulaiman; Ahmad, Anuar; Sulaiman, Shahril Irwan (2006)
A charge controller unit can be thought off as the brain in a solar photovoltaic (PV) system. An earlier project on a charge controller has been done using the simple ON-OFF system. In this project, the controller is upgraded using fuzzy algorithm. This fuzzy-logic based charge controller provides a higher class of intelligence to the system. Besides controlling the charging-discharging of the integral battery like many commercial charge controller, the functions of the this fuzzy-based charge controller includes switching the available option loads, protecting batteries and wiring, monitoring the performance of the system and giving warnings when the system is having problems. It works by monitoring the ramping of charging-discharging regimes in the PV system and gives the appropriate signals in terms of switching ON or OFF the energy flow in the PV system. This report presents and discusses the design, fabrication, assembly, commissioning and testing of a prototype fuzzy-logic based charge controller for a hybrid photovoltaic system.